Spatiotemporal dependence of compound drought–heatwave and fire activity in China - Zitong Shi; Dabang Jiang; Yongli Wang (Weather and Climate Extremes, 2024)
Climate strongly influences fire activity, and the alignment of multiple weather and climate extremes, such as co-occurrence of hot and dry, leads to more severe fires. Recognizing the knowledge gap on the combination of compound drought–heatwave events and fire activities, we applied an event coincidence analysis to investigate their spatiotemporal dependence in China during 2003–2020 based on remote sensing active fire data and 2 206-site meteorological observations. It is found that the spatial extent of fire activities and their simultaneous occurrence with compound drought–heatwaves both expanded. The geographical hotspots of frequent fire activities following compound drought–heatwave events were predominantly situated in southwestern and southern China. There was a significant upward trend of fire activities following compound drought–heatwave events, with the ratio of compound drought–heatwave events being followed by fire activities reached 0.70 ± 0.06 in 2013–2020, indicating a growth of 19% compared to the period of 2003–2012. Our findings contribute to a better understanding of the spatiotemporal dependence of compound drought–heatwave and fire activity and provide insights into their mitigation strategies.